A kind of water-based inorganic zinc-rich anticorrosive coating and preparation method thereof

By freeze-thawing cycle and microwave plasma treatment on Mxene, combined with other raw materials, an aqueous inorganic zinc-rich anti-corrosion coating was prepared, which solved the problem of insufficient anti-slip performance of traditional coatings in high heat and high humidity environments, and achieved excellent anti-corrosion and anti-slip performance, meeting the long-term use needs of large-scale building steel components.

CN119662060BActive Publication Date: 2025-04-25GUOKE XIANCAI (HEFEI) TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510197091.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-04-25
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

Traditional water-based inorganic zinc-rich anti-corrosion coatings have insufficient anti-slip performance and stability in high heat and high humidity environments, resulting in the coating slipping and peeling, and the anti-corrosion performance is reduced, making it difficult to meet the high requirements of high-strength bolt connections facing friction coefficient.

Method used

Mxene was modified by freeze-thaw cycle treatment and microwave plasma treatment, and combined with silicate solution, zinc powder and additives, an aqueous inorganic zinc-rich anticorrosion coating was prepared.

Benefits of technology

It significantly improves the anti-slip performance stability of water-based inorganic zinc-rich anti-corrosion coatings under high heat and humidity conditions, and gives them excellent anti-corrosion and anti-slip performance, meeting the long-term use needs of large-scale building steel components in harsh environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a water-based inorganic zinc-rich anticorrosion coating and a preparation method thereof, and relates to the technical field of anticorrosion coatings. The water-based inorganic zinc-rich anticorrosion coating comprises the following raw materials, by weight: 20 to 30 parts of silicate solution, 40 to 55 parts of zinc powder, 7 to 16 parts of modified Mxene, and 0.3 to 0.8 parts of an auxiliary agent; the modified Mxene is obtained by sequentially subjecting Mxene to freeze-thaw cycle treatment and microwave plasma treatment. On the basis of the existing water-based inorganic zinc-rich anticorrosion coating, the present invention not only significantly improves the anti-slip performance stability of the obtained water-based inorganic zinc-rich anticorrosion coating under extreme conditions such as high heat and high humidity, but also gives it excellent anticorrosion and anti-slip properties, which can meet the long-term use requirements of various large-scale steel components in harsh environments, and makes up for the shortcomings of the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion coatings, and in particular to a water-based inorganic zinc-rich anti-corrosion coating and a preparation method thereof. Background Art

[0002] In the field of anti-corrosion coating technology, water-based inorganic zinc-rich anti-corrosion coatings are widely used in the anti-corrosion protection of various large-scale steel components due to their environmental protection and excellent corrosion resistance, especially the high-strength bolt connection surfaces of steel components such as bridges and prefabricated buildings, which have extremely strict performance requirements for anti-corrosion coatings. After spraying the anti-corrosion coating on the high-strength bolt connection surface, the friction coefficient is usually required to be no less than 0.55 to ensure the stability and safety of the connection surface.

[0003] However, with the increasingly harsh use environment, especially under extreme climatic conditions such as high heat and high humidity, traditional water-based inorganic zinc-rich anti-corrosion coatings have gradually exposed their shortcomings in terms of anti-slip performance stability, anti-corrosion performance, and anti-skid performance. Although traditional water-based inorganic zinc-rich anti-corrosion coatings have a certain anti-corrosion effect, when subjected to extreme environmental conditions such as high heat and high humidity for a long time, their coatings are prone to slippage and peeling, resulting in a significant decrease in anti-corrosion performance. At the same time, the anti-slip performance of traditional coatings is often difficult to meet the needs of specific usage scenarios, especially the high requirements for friction coefficients faced by high-strength bolt connections, which poses a hidden danger to the safe use of large-scale steel components in buildings.

[0004] At present, the development of water-based inorganic zinc-rich anti-corrosion coatings is moving towards a more efficient, environmentally friendly and durable direction. Various water-based inorganic zinc-rich anti-corrosion coatings are emerging in the market. They have improved anti-corrosion performance and construction performance, but their anti-slip performance stability under high heat and humidity conditions is poor, and they cannot meet the special needs of high-strength bolt connection surfaces for steel components such as bridges and prefabricated buildings. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a water-based inorganic zinc-rich anti-corrosion coating and a preparation method thereof.

[0006] In a first aspect, the present invention provides a water-based inorganic zinc-rich anti-corrosion coating, which comprises the following raw materials in parts by weight:

[0007] 20-30 parts of silicate solution, 40-55 parts of zinc powder, 7-16 parts of modified Mxene and 0.3-0.8 parts of additives;

[0008] The modified Mxene is obtained by subjecting Mxene to freeze-thaw cycle treatment and microwave plasma treatment in sequence.

[0009] Furthermore, the water-based inorganic zinc-rich anticorrosive coating comprises the following raw materials in parts by weight:

[0010] 26.5 parts of silicate solution, 47 parts of zinc powder, 11 parts of modified Mxene and 0.5 parts of additives.

[0011] Furthermore, the working condition parameters of the freeze-thaw cycle treatment include: freezing temperature of -35~-25°C, freezing time of 30~60 minutes, thawing temperature of 30~40°C, thawing time of 30~60 minutes, and the number of cycle treatments of 4~8 times.

[0012] Furthermore, the working condition parameters of the microwave plasma treatment include: the working mode is open to atmospheric pressure, the microwave treatment power is 970~1250 W, the working medium is air, and the treatment time is 60~180 seconds.

[0013] Furthermore, the preparation of the silicate solution includes the following process:

[0014] Sodium hydroxide, potassium hydroxide and water are stirred and mixed in a molar ratio of (0.2-0.4):(0.6-0.8):(7-13) to obtain a premixed solution;

[0015] The premixed liquid is added dropwise into a silica sol that accounts for 12 to 16 times the total molar amount of the sodium hydroxide and the potassium hydroxide, and then heated and stirred at a temperature of 48 to 55° C. for 60 to 90 minutes to obtain the silicate solution.

[0016] Furthermore, the particle size of the zinc powder is 300-500 mesh.

[0017] Furthermore, the auxiliary agent is composed of a defoamer, a dispersant and an anti-settling agent in a weight ratio of (1-2): (0.5-1.2): (2-3).

[0018] Further, the defoaming agent includes at least one of BYK-024 and BYK-1789, the dispersant includes at least one of BYK-110 and BYK-203, and the anti-settling agent includes at least one of bentonite and white carbon black.

[0019] In a second aspect, the present invention provides a method for preparing the water-based inorganic zinc-rich anticorrosive coating according to any one of the first aspects, the preparation method comprising the following steps:

[0020] The Mxene is subjected to freeze-thaw cycle treatment and microwave plasma treatment in sequence to obtain modified Mxene;

[0021] The modified Mxene and zinc powder are stirred and mixed to obtain a first mixture;

[0022] Stirring and mixing the silicate solution and the auxiliary agent to obtain a second mixed material;

[0023] The first mixed material and the second mixed material are stirred and mixed to obtain the water-based inorganic zinc-rich anti-corrosion coating.

[0024] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:

[0025] The embodiment of the present invention provides a water-based inorganic zinc-rich anti-corrosion coating and a preparation method thereof. The present invention modifies MXene by combining a freeze-thaw cycle treatment process and a microwave plasma treatment process, which not only improves the sensitivity of the MXene material itself to temperature and humidity, but also improves the compatibility of MXene in the water-based inorganic zinc-rich anti-corrosion coating and enhances its interfacial interaction with silicate solution, zinc powder and additives, thereby improving the anti-slip performance stability of the obtained water-based inorganic zinc-rich anti-corrosion coating under extreme conditions such as high heat and high humidity and giving it excellent anti-corrosion and anti-slip properties, which can meet the long-term use requirements of various large-scale building steel components in harsh environments, and make up for the shortcomings of the prior art. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0028] In a first aspect, the present invention provides a water-based inorganic zinc-rich anti-corrosion coating, which comprises the following raw materials in parts by weight:

[0029] 20-30 parts of silicate solution, 40-55 parts of zinc powder, 7-16 parts of modified Mxene and 0.3-0.8 parts of additives;

[0030] The modified Mxene is obtained by subjecting Mxene to freeze-thaw cycle treatment and microwave plasma treatment in sequence.

[0031] The embodiment of the present invention provides a water-based inorganic zinc-rich anti-corrosion coating. The present invention modifies MXene by combining a freeze-thaw cycle treatment process and a microwave plasma treatment process, which not only improves the sensitivity of the MXene material itself to temperature and humidity, but also improves the compatibility of MXene in the water-based inorganic zinc-rich anti-corrosion coating and enhances its interfacial interaction with silicate solution, zinc powder and additives, thereby improving the anti-slip performance stability of the obtained water-based inorganic zinc-rich anti-corrosion coating under extreme conditions such as high heat and high humidity and giving it excellent anti-corrosion and anti-slip properties, which can meet the long-term use requirements of various large-scale building steel components in harsh environments, and make up for the shortcomings of the prior art.

[0032] In the present invention, Mxene is a two-dimensional transition metal carbide or carbonitride with a unique layered structure, which can be directly prepared by commercial products or by the hydrofluoric acid etching method disclosed in the prior art. Specifically, in the following embodiments and comparative examples, Mxene is prepared by the following method: 2g of MAX phase powder Ti3AlC2 is dispersed in a LiF+HCl mixed reagent (obtained by adding 3.6gLiF to 40mL of 9mol / L HCl solution and stirring and mixing) and an etching reaction is carried out for 24h to obtain a first mixed solution, and the first mixed solution is stirred at a temperature of 25°C to obtain a second mixed solution; the second mixed solution is centrifuged and washed with deionized water at a speed of 3500rpm until the pH of the supernatant of the second mixed solution is 6, and the precipitate of the second mixed solution at this moment is obtained; the precipitate is added to deionized water and shaken for 10 minutes and centrifuged at 3500rpm for 60 minutes, and the upper suspension is dried in a vacuum drying oven at 40°C to obtain MXene.

[0033] In some specific embodiments, the water-based inorganic zinc-rich anti-corrosion coating comprises the following raw materials in parts by weight:

[0034] 26.5 parts of silicate solution, 47 parts of zinc powder, 11 parts of modified Mxene and 0.5 parts of additives.

[0035] In some specific embodiments, the working condition parameters of the freeze-thaw cycle treatment include: freezing temperature of -35~-25°C, freezing time of 30~60 minutes, thawing temperature of 30~40°C, thawing time of 30~60 minutes, and the number of cycle treatments is 4~8 times.

[0036] In some specific embodiments, the working condition parameters of the microwave plasma treatment include: the working mode is open to atmospheric pressure, the microwave treatment power is 970~1250 W, the working medium is air, and the treatment time is 60~180 seconds.

[0037] In some specific embodiments, the preparation of the silicate solution comprises the following process:

[0038] Sodium hydroxide, potassium hydroxide and water are stirred and mixed in a molar ratio of (0.2-0.4):(0.6-0.8):(7-13) to obtain a premixed solution;

[0039] The premixed liquid is added dropwise into a silica sol that accounts for 12 to 16 times the total molar amount of the sodium hydroxide and the potassium hydroxide, and then heated and stirred at a temperature of 48 to 55° C. for 60 to 90 minutes to obtain the silicate solution.

[0040] In some specific embodiments, the particle size of the zinc powder is 300-500 mesh.

[0041] In some specific embodiments, the auxiliary agent is composed of a defoaming agent, a dispersant and an anti-settling agent in a weight ratio of (1-2): (0.5-1.2): (2-3).

[0042] In some specific embodiments, the defoaming agent includes at least one of BYK-024 and BYK-1789, the dispersant includes at least one of BYK-110 and BYK-203, and the anti-settling agent includes at least one of bentonite and white carbon black.

[0043] In the second aspect, based on the same inventive concept, the present invention provides a method for preparing the water-based inorganic zinc-rich anticorrosive coating according to any one of the first aspects, the preparation method comprising the following steps:

[0044] The Mxene is subjected to freeze-thaw cycle treatment and microwave plasma treatment in sequence to obtain modified Mxene;

[0045] The modified Mxene and zinc powder are stirred and mixed to obtain a first mixture;

[0046] Stirring and mixing the silicate solution and the auxiliary agent to obtain a second mixed material;

[0047] The first mixed material and the second mixed material are stirred and mixed to obtain the water-based inorganic zinc-rich anti-corrosion coating.

[0048] The preparation method of the water-based inorganic zinc-rich anti-corrosion coating provided by the present invention is simple to operate, does not require additional specific equipment, and is suitable for industrial mass production; at the same time, the preparation method is based on the water-based inorganic zinc-rich anti-corrosion coating described in any one of the first aspects, and therefore has at least the beneficial effects of the water-based inorganic zinc-rich anti-corrosion coating described in any one of the first aspects, which will not be repeated here.

[0049] It should be noted that the components and raw materials involved in the water-based inorganic zinc-rich anti-corrosion coating and the preparation method thereof provided in the embodiments of the present invention, unless otherwise specified or specifically described, can be directly commercially available products or homemade using existing public preparation methods; at the same time, the steps and parameters involved, unless otherwise specified or specifically described, can be carried out according to the preparation process and parameter conditions disclosed in the prior art or directly using existing equipment, and the present invention document will not repeat them one by one.

[0050] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed. Example 1

[0051] This example provides a water-based inorganic zinc-rich anti-corrosion coating, which includes the following raw materials in parts by weight:

[0052] 26.5 parts of silicate solution, 47 parts of zinc powder, 11 parts of modified Mxene and 0.5 parts of additives;

[0053] The preparation of the silicate solution includes the following process: stirring and mixing sodium hydroxide, potassium hydroxide and water in a molar ratio of 0.3:0.7:10 to obtain a premixed solution; dropping the premixed solution into a silica sol accounting for 15 times the total molar amount of the sodium hydroxide and the potassium hydroxide, and then heating and stirring at a temperature of 50° C. for 75 minutes to obtain the silicate solution;

[0054] The particle size of the zinc powder is 400 mesh;

[0055] The modified Mxene is obtained by sequentially subjecting Mxene to freeze-thaw cycle treatment and microwave plasma treatment, and comprises the following processes: subjecting Mxene to freeze-thaw cycle treatment, wherein the freezing temperature is -30°C, the freezing time is 45 minutes, the thawing temperature is 35°C, the thawing time is 45 minutes, and the number of cycle treatments is 6 times, to obtain the first Mxene; placing the first Mxene in a microwave plasma device for microwave plasma treatment, wherein the working mode is atmospheric pressure open, the microwave treatment power is 1100 W, the working medium is air, and the treatment time is 90 seconds, to obtain the modified Mxene;

[0056] The auxiliary agent is composed of a defoamer, a dispersant and an anti-settling agent in a weight ratio of 1.5:0.8:2.5. The defoamer is BYK-1789, the dispersant is BYK-203, and the anti-settling agent is bentonite.

[0057] The preparation method of the above-mentioned water-based inorganic zinc-rich anticorrosive coating comprises the following steps:

[0058] Obtaining modified Mxene;

[0059] The modified Mxene and zinc powder are stirred and mixed to obtain a first mixture;

[0060] Stirring and mixing the silicate solution and the auxiliary agent to obtain a second mixed material;

[0061] The first mixed material and the second mixed material are stirred and mixed to obtain the water-based inorganic zinc-rich anti-corrosion coating. Example 2

[0062] This example provides a water-based inorganic zinc-rich anti-corrosion coating, which includes the following raw materials in parts by weight:

[0063] 20 parts of silicate solution, 40 parts of zinc powder, 7 parts of modified Mxene and 0.3 parts of additives;

[0064] The preparation of the silicate solution includes the following process: stirring and mixing sodium hydroxide, potassium hydroxide and water in a molar ratio of 0.2:0.6:7 to obtain a premixed solution; dropping the premixed solution into a silica sol accounting for 12 times the total molar amount of the sodium hydroxide and the potassium hydroxide, and then heating and stirring at a temperature of 48° C. for 90 minutes to obtain the silicate solution;

[0065] The particle size of the zinc powder is 300 mesh;

[0066] The modified Mxene is obtained by sequentially subjecting Mxene to freeze-thaw cycle treatment and microwave plasma treatment, and comprises the following processes: subjecting Mxene to freeze-thaw cycle treatment, wherein the freezing temperature is -35°C, the freezing time is 30 minutes, the thawing temperature is 40°C, the thawing time is 30 minutes, and the number of cycle treatments is 4 times, thereby obtaining the first Mxene; placing the first Mxene in a microwave plasma device for microwave plasma treatment, wherein the working mode is atmospheric pressure open, the microwave treatment power is 1250 W, the working medium is air, and the treatment time is 60 seconds, thereby obtaining the modified Mxene;

[0067] The auxiliary agent is composed of a defoamer, a dispersant and an anti-settling agent in a weight ratio of 1:0.5:2. The defoamer is BYK-024, the dispersant is BYK-110, and the anti-settling agent is white carbon black.

[0068] The preparation method of the above-mentioned water-based inorganic zinc-rich anti-corrosion coating is the same as that of Example 1. Example 3

[0069] This example provides a water-based inorganic zinc-rich anti-corrosion coating, which includes the following raw materials in parts by weight:

[0070] 30 parts of silicate solution, 55 parts of zinc powder, 16 parts of modified Mxene and 0.8 parts of additives;

[0071] The preparation of the silicate solution includes the following process: stirring and mixing sodium hydroxide, potassium hydroxide and water in a molar ratio of 0.4:0.8:13 to obtain a premixed solution; dropping the premixed solution into a silica sol accounting for 16 times the total molar amount of the sodium hydroxide and the potassium hydroxide, and then heating and stirring at a temperature of 55° C. for 60 minutes to obtain the silicate solution;

[0072] The particle size of the zinc powder is 500 mesh;

[0073] The modified Mxene is obtained by sequentially subjecting Mxene to freeze-thaw cycle treatment and microwave plasma treatment, and comprises the following processes: subjecting Mxene to freeze-thaw cycle treatment, wherein the freezing temperature is -25°C, the freezing time is 60 minutes, the thawing temperature is 30°C, the thawing time is 60 minutes, and the number of cycle treatments is 8 times, thereby obtaining the first Mxene; placing the first Mxene in a microwave plasma device for microwave plasma treatment, wherein the working mode is atmospheric pressure open, the microwave treatment power is 970 W, the working medium is air, and the treatment time is 180 seconds, thereby obtaining the modified Mxene;

[0074] The auxiliary agent is composed of a defoamer, a dispersant and an anti-settling agent in a weight ratio of 2:1.2:3. The defoamer is BYK-024, the dispersant is BYK-110, and the anti-settling agent is white carbon black.

[0075] The preparation method of the above-mentioned water-based inorganic zinc-rich anti-corrosion coating is the same as that of Example 1.

[0076] Comparative Example 1

[0077] This example provides a water-based inorganic zinc-rich anti-corrosion coating and a preparation method thereof, which is different from Example 1 only in that the modified Mxene is adjusted to unmodified Mxene and the preparation step of the modified Mxene is omitted accordingly; the remaining steps and parameters are the same.

[0078] Comparative Example 2

[0079] This example provides a water-based inorganic zinc-rich anti-corrosion coating and a preparation method thereof, which is different from Example 1 only in that the modified Mxene is obtained by subjecting Mxene to only freeze-thaw cycle treatment and the microwave plasma treatment step is omitted accordingly; the remaining steps and parameters are the same.

[0080] Comparative Example 3

[0081] This example provides a water-based inorganic zinc-rich anti-corrosion coating and a preparation method thereof, which is different from Example 1 only in that the modified Mxene is obtained by subjecting Mxene to microwave plasma treatment only and the freeze-thaw cycle treatment step is omitted accordingly; the remaining steps and parameters are the same.

[0082] Test Case

[0083] This example examines the anti-slip performance stability of the water-based inorganic zinc-rich anti-corrosion coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 3 under high heat and high humidity conditions.

[0084] The test method is as follows:

[0085] 1) Initial anti-skid friction coefficient test: According to the GB / T 9263-2020 test standard, the anti-skid friction coefficient of the water-based inorganic zinc-rich anti-corrosion coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 3 was tested and recorded as the anti-skid friction coefficient M1 before high heat and high humidity treatment;

[0086] 2) High heat and high humidity accelerated treatment: The test sample coatings formed by the water-based inorganic zinc-rich anti-corrosion coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were placed in a high temperature environment of 400° C. and a high humidity condition of 85% relative humidity, respectively, for a period of 45 minutes of accelerated treatment, and then the anti-slip friction coefficient M2 after high heat and high humidity treatment was measured again according to the GB / T 9263-2020 test standard;

[0087] 3) Calculation of anti-skid friction coefficient retention rate: According to the formula: anti-skid friction coefficient retention rate (%) = M2 / M1×100%, the anti-skid friction coefficient retention rate of each case is calculated; the higher the anti-skid friction coefficient retention rate, the better the stability of its anti-skid performance.

[0088] The test results are shown in Table 1.

[0089] Table 1

[0090] Test samples Anti-skid friction coefficient retention rate (%) Example 1 96.7 Example 2 88.5 Example 3 92.3 Comparative Example 1 24.9 Comparative Example 2 35.2 Comparative Example 3 40.6

[0091] It can be seen from Table 1 that, compared with Comparative Examples 1 to 3, the water-based inorganic zinc-rich anti-corrosion coatings provided by Examples 1 to 3 of the present invention have better anti-slip performance stability under high heat and high humidity conditions, and the anti-slip friction coefficient retention rate (%) is maintained at 88.5% to 96.7%; and the anti-slip friction coefficient M1 of the water-based inorganic zinc-rich anti-corrosion coating obtained in Example 1 is as high as 0.68, which meets the long-term use requirements of various large-scale building steel components in harsh environments.

[0092] In addition, this example also carried out a salt spray resistance test on the waterborne inorganic zinc-rich anti-corrosion coatings obtained in Examples 1 to 3 according to the GB / T10125 test standard. The test results showed that the salt spray resistance time (h) was between 3750 and 3920, indicating that the waterborne inorganic zinc-rich anti-corrosion coatings obtained in the examples of the present invention have excellent anti-corrosion performance.

[0093] In summary, the embodiments of the present invention provide a water-based inorganic zinc-rich anti-corrosion coating and a preparation method thereof. Based on the existing water-based inorganic zinc-rich anti-corrosion coating, the present invention introduces a specific modified Mxene, which not only significantly improves the anti-slip performance stability of the obtained water-based inorganic zinc-rich anti-corrosion coating under extreme conditions such as high heat and high humidity, but also gives it excellent anti-corrosion and anti-slip properties, which can meet the long-term use requirements of various large-scale building steel components in harsh environments, and makes up for the shortcomings of the prior art.

[0094] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0095] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A water-based inorganic zinc-rich anticorrosive coating, characterized in that: The water-based inorganic zinc-rich anticorrosive coating comprises the following raw materials in parts by weight: 20-30 parts of silicate solution, 40-55 parts of zinc powder, 7-16 parts of modified Mxene and 0.3-0.8 parts of additives; The modified Mxene is obtained by subjecting Mxene to freeze-thaw cycle treatment and microwave plasma treatment in sequence.

2. The water-based inorganic zinc-rich anticorrosive coating according to claim 1, characterized in that: The water-based inorganic zinc-rich anticorrosive coating comprises the following raw materials in parts by weight: 26.5 parts of silicate solution, 47 parts of zinc powder, 11 parts of modified Mxene and 0.5 parts of additives.

3. The water-based inorganic zinc-rich anticorrosive coating according to claim 1, characterized in that: The working condition parameters of the freeze-thaw cycle treatment include: a freezing temperature of -35 to -25°C, a freezing time of 30 to 60 minutes, a thawing temperature of 30 to 40°C, a thawing time of 30 to 60 minutes, and a cycle treatment number of 4 to 8 times.

4. The water-based inorganic zinc-rich anticorrosive coating according to claim 1, characterized in that: The working condition parameters of the microwave plasma treatment include: the working mode is open to atmospheric pressure, the microwave treatment power is 970-1250 W, the working medium is air, and the treatment time is 60-180 seconds.

5. The water-based inorganic zinc-rich anticorrosive coating according to claim 1, characterized in that: The preparation of the silicate solution comprises the following process: Stir and mix sodium hydroxide, potassium hydroxide and water in a molar ratio of (0.2-0.4):(0.6-0.8):(7-13) to obtain a premixed solution; The premixed liquid is added dropwise into a silica sol that accounts for 12 to 16 times the total molar amount of the sodium hydroxide and the potassium hydroxide, and then heated and stirred at a temperature of 48 to 55° C. for 60 to 90 minutes to obtain the silicate solution.

6. The water-based inorganic zinc-rich anticorrosive coating according to claim 1, characterized in that: The particle size of the zinc powder is 300-500 meshes.

7. The water-based inorganic zinc-rich anticorrosive coating according to claim 1, characterized in that: The auxiliary agent is composed of a defoamer, a dispersant and an anti-settling agent in a weight ratio of (1-2): (0.5-1.2): (2-3).

8. The water-based inorganic zinc-rich anticorrosive coating according to claim 7, characterized in that: The defoaming agent includes at least one of BYK-024 and BYK-1789, the dispersant includes at least one of BYK-110 and BYK-203, and the anti-settling agent includes at least one of bentonite and white carbon black.

9. A method for preparing the water-based inorganic zinc-rich anticorrosive coating according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: The Mxene is subjected to freeze-thaw cycle treatment and microwave plasma treatment in sequence to obtain modified Mxene; The modified Mxene and zinc powder are stirred and mixed to obtain a first mixture; Stirring and mixing the silicate solution and the auxiliary agent to obtain a second mixed material; The first mixed material and the second mixed material are stirred and mixed to obtain the water-based inorganic zinc-rich anti-corrosion coating.

Citation Information

Patent Citations

  • Method for preparing pure-phase MXene by using plasma etching technology

    CN111847456A

  • Preparation method of MXene nanosheet

    CN116605880A